Colorectal polyps increase the glycolytic activity - Rebane-Klemm, Egle; Reinsalu, Leenu; Puurand, Marju; Shevchuk, Igor; Bogovskaja, Jelena; Suurmaa, Kulliki; Valvere, Vahur; Moreno-Sanchez, Rafael; Kaambre, Tuuli (Frontiers in Oncology, 2023)
In colorectal cancer (CRC) energy metabolism research, the precancerous stage of polyp has remained rather unexplored. By now, it has been shown that CRC has not fully obtained the glycolytic phenotype proposed by O. Warburg and rather depends on mitochondrial respiration. However, the pattern of metabolic adaptations during tumorigenesis is still unknown. Understanding the interplay between genetic and metabolic changes that initiate tumor development could provide biomarkers for diagnosing cancer early and targets for new cancer therapeutics. We used human tissue material from CRC and polyp patients and performed analysis to detect changes on molecular and functional levels with the goal of generally describing metabolic reprogramming in polyp and cancer tissue. Colon polyps were found to have a more glycolytic bioenergetic phenotype than tumors and normal tissues. This was supported by a greater GLUT1, HK, LDHA, and MCT expression. Despite the increased glycolytic activity, cells in polyps were still able to maintain a highly functional OXPHOS system. The mechanisms of OXPHOS regulation and the preferred substrates are currently unclear and would require further investigation. During polyp formation, intracellular energy transfer pathways become rearranged mainly by increasing the expression of mitochondrial adenylate kinase (AK) isoforms and creatine kinase (CK) isoforms. Decreased glycolysis and maintenance of OXPHOS activity, together with the downregulation of the CK system and the most common AK isoforms (AK1 and AK2), seem to play a relevant role in CRC development.